2003
DOI: 10.1081/prg-120024027
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Uterine Perfusion in the Second Trimester Is Not Associated with Neutrophil Activation

Abstract: Pathological uterine perfusion in the second trimester was not associated with maternal neutrophil activation. The measurement of the MPO and PMN elastase concentration suggested that neutrophil activation in preeclampsia or IUGR is a secondary effect of the disease rather than a primary pathophysiological factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The maternal plasma levels of neutrophil elastase may serve as a possible cell-free marker to quantify neutrophil activation as demonstrated in women with PE. The neutrophil elastase levels were elevated in both early-and lateonset forms of PE [7,22] . Neutrophils, but not lymphocytes or monocytes, infiltrate maternal systemic vasculature causing the majority of vascular cell dysfunction in women with PE [23] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The maternal plasma levels of neutrophil elastase may serve as a possible cell-free marker to quantify neutrophil activation as demonstrated in women with PE. The neutrophil elastase levels were elevated in both early-and lateonset forms of PE [7,22] . Neutrophils, but not lymphocytes or monocytes, infiltrate maternal systemic vasculature causing the majority of vascular cell dysfunction in women with PE [23] .…”
Section: Discussionmentioning
confidence: 98%
“…Many investigators [5,6] reported sVEGFR-1 as a possible PE factor. Increased neutrophils have been demonstrated in women with PE, and neutrophil activation liberates neutrophil elastase [7] . Hence, in this study, we assessed these biochemical markers in the umbilical cord and placenta of preeclamptic patients, and evaluated their impact on the mother and fetus.…”
Section: Introductionmentioning
confidence: 99%
“…Since the number of altered markers in maternal plasma as well as in the placenta is enormous and various metabolic, endocrine and neuro-vegetative axes are infl uenced, it is diffi cult at this stage of the disease to differentiate between etiological factors, relevant pathophysiological factors and secondary phenomena that are not linked to the cause of the disease. For instance, factors like neutrophil activation that have been discussed as relevant pathophysiological parameters are not present until clinical manifestation and thus are part of the syndrome and not the cause of the disease (Stepan et al 2003). As a consequence, this complex dysregulation of the maternal organism does not seem to be a promising target for preeclampsia research in terms of the etiology.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…However, in a recent study of our group including 50 patients, pathological uterine perfusion in the second trimester was not associated with maternal neutrophil activation. The measurement of the MPO and PMN elastase concentration suggested that neutrophil activation in preeclampsia is a secondary effect of the disease rather than a primary pathophysiological factor (Stepan et al 2003).…”
Section: Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation